The Impact of East Cashew Social Entrepreneurship On Pro-Poor Tour-ism In Karangasem Regency - Mananda, I Gusti Putu Bagus Sasrawan (Eduvest - Journal of Universal Studies, 2023)
Based on data, there are more than 28 thousand residents in Karangasem, Bali, who live below the poverty line. This poverty occurs because residents who were previously in-volved in the tourism industry cannot meet their basic needs, with the average monthly per capita expenditure below the poverty line. Karangasem was chosen deliberately as a research location because it has the lowest human development index in Bali. The re-search sample was taken randomly from poor households who previously worked in the tourism sector and are now laid off as informants. Further data was collected through structured interviews and observations. The results of data analysis and discussion show that the entrepreneurial welfare project in East Bali identified two strategies for reducing poverty. First, cluster one is a strategy for poor households who are very poor and have a low level of education. In situations of economic and social limitations, it is necessary to channel employment opportunities through a job placement system for this type of house-hold. They are given the opportunity to produce goods for certain companies, involving three parties: poor individuals, companies, and the government. Second, cluster two is a strategy for poor individuals who work independently to increase their income. For entre-preneurial households, are advised to develop their businesses into micro, small and me-dium businesses to increase sales. This strategy focuses on improving quality in the pro-duction, marketing and financing processes. The second cluster strategy is a model of rural community empowerment based on partnerships.